681 Return-to-work interventions for employees with burnout: a systematic review. (24th April 2018) - Lambreghts, C; Vandenbroeck, S; Godderis, L
Abstract : Introduction: Burnout is a work-related mental health problem and may cause long-term sickness absence. Return-to-work interventions for burned out employees on sick leave aim to prevent long-term work disability. This systematic review adresses 2 questions: Which return–to–work interventions for burned out employees on sick leave have been studied? What is the effect of these interventions on return to work? Methods: We performed a systematic literature review and searched Medline, CINAHL, EMBASE and Web of Science from Jan 1, 2000 to March 16, 2016. We searched for articles of return-to-work interventions for burned out employees on sick leave. We excluded studies of self-employed people and studies of employees suffering from mental health problems other than burnout. We conducted the review in line with the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. Outcomes were return to work and overall burnout symptoms. Results: We identified 1578 articles after removal of all duplicates. Ten articles met inclusion criteria of which 5 were person-directed interventions, 2 were organisation-directed and 3 were a combination of both intervention types. None of the person-directed interventions caused a significant improvement in return to work. In contrast, the 2 organisation-directed and 2 of the 3 combined interventions did significantly improve return to work. All interventions had a positive effect on overall burnout symptoms. Discussion: Although all interventions improved burnout symptoms, only the interventions that were (partly) organisation-directed had a positive effect on return to work. This finding is important in the development of return-to-work interventions for employees with burnout.